Tinjauan Tentang Keberadaan Lembaga Negara Non Struktural Dalam Sistem Pemerintahan Indonesia - Rosidi, Rosidi (Sekolah Tinggi Ilmu Pemerintahan Abdi Negara, 2015)
The emergence of the phenomenon of the presence of non-structural institution (LNS) indicates that there are still many problems that can not be solved by State institutions that exist, so the presence of non-structural institution is still needed and does not conflict with the Constitution of 1945. The presence of LNS cause problems including the overlap (overlapping) between LNS with LNS authority or other state institutions. Likewise, the legal basis for the establishment of very varide. Analysis of the problem that needs to be done is mapping the LNS and an exsting state agency so as to avoid overlapping. The legal basis for the establishment of uniform LNS in the form of law, goverment regulation, Decree of the President or the Presidential Decree. In addition, the feasibilty of establishing LNS is done based on Kolabarasi thingking among goverments, communities and businesses that its presence is highly expected by all parties.